Document Based Text Data Security Using the Prime Generator Algorithm Fermat's and the ElGamal Algorithm - Andre Gusli Agus Riadi; Mhd.Furqan; Rakhmat Kurniawan (Sean Institute, 2021)
Elgamal is an asymmetric key cryptography algorithm, which means that Elgamal cryptography requires two keys to perform the encryption and description processes, while the key used in the Elgamal algorithm is the public key for encryption while the private key is for decryption. The public key and private key are obtained using the help of other algorithms, one of which is the fermat prime generator algorithm, this fermat prime generator algorithm has a role to find prime random numbers where the randomized prime numbers obtained are used to form the public and private keys. In this study, the researcher wants to combine these two algorithms to secure text-based document files. The result of this research is an application that can secure text-based document files.